THE EXCURSION METHOD IN TEACHING PHYSICS - Jamshid Ergashev Kuldoshevich (Bright Mind Publishing, 2025)
This article explores the use of excursions as an effective method for teaching physics in general secondary schools. Excursions, defined as organized visits to museums, exhibitions, historical sites, or other notable locations, serve as a dynamic tool for enhancing students' understanding of natural phenomena and scientific principles. The article highlights the importance of excursions in activating students' exploratory skills, connecting theoretical knowledge with real-world applications, and fostering a deeper appreciation for the role of physics in technology and everyday life. It also discusses the historical development of excursion methods in physics education, referencing the works of prominent educators and researchers. The article emphasizes the need to expand the use of excursions in the curriculum, despite current limitations, and underscores their potential to improve students' motivation, critical thinking, and engagement with the subject.
Keywords: Physics education, excursion method, active learning, extracurricular activities, scientific exploration, student motivation, real-world applications, pedagogical methods.